Studi Penataan Kawasan Simpang Ciawi sebagai Simpul Transportasi - Ashab, Muhammad Mauludhy; Murtejo, Tedy; Alimuddin, Alimuddin; Sudrajat, Endang (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
Abstract: In 2016 Bogor City was named the city with the 2nd worst traffic in the world by the Waze version. One of the worst congestion points in the Puncak Bogor area is the Ciawi Intersection which is located in Harjasari, Bogor Selatan District, Bogor City. The purpose of this study was to determine and analyze the performance of the road sections and intersection performance, to identify and analyze the location of the transportation nodes, and to analyze the land use allocation at the Ciawi intersection. The method used in this study is collecting primary data such as traffic volume, traffic speed, and traffic capacity, through a traffic survey followed by data processing using the MKJI 1997 technical guidelines. Based on the analysis results, there are 2 roads with service level C: the Jagorawi toll road section and the Gadog st., and 2 roads with a service level F: Tajur st., and Cibadak st. As for the level of intersection service, there are 3 roads with an F value: Jagorawi toll road, Cibadak st., and Gadog Puncak st. with successive delays of 156.64 seconds, 282.15 seconds and 243.01 seconds. Tajur st. intersection received a service level score of B’s, with a delay of 6.90 seconds. The planned location of the transportation node at the Ciawi intersection is located at coordinates 6o39’20.89” S; 106o50’49.76” E. The land use allocation in the Simpang Ciawi area is in accordance with the structure and pattern of spatial use based on the Bogor City and Bogor Regency development plans, both related to the planning of transportation nodes in the area and the current use of the land.